PENGARUH GENDER, TEKANAN KETAATAN, INDEPENDENSI, TEKANAN ANGGARAN WAKTU, DAN PENGALAMAN AUDITOR TERHADAP AUDIT JUDGMENT (Studi Empiris Pada Auditor Kantor Akuntan Publik Di Wilayah Surabaya) - Mukhyi, Ramdani Abdullah; Widiastoeti, Hendy (Universitas 17 Agustus 1945 Surabaya, 2019)
ABSTRACTAuditor must always have the nature and character (Gender) whether men and women in making decisions or audit judgment. And auditors should follow the rules and policies and applicable regulations in Indonesia, if the auditor comply (Pressure Obedience) regulation it certainly will occur independent character in taking decisions (audit Judgment) accurate. If an independent identity is formed in the auditor the company's health will be better again. The auditor also should be able to share time in taking decisions affecting the value of the services because negotiated between the client (Time Budget Pressure) allow for quicker completion and immediately take a decision (judgment audits) within the deadline specified by the client. Not only this, but of all of them, in the auditor's experience can also influence the decision where to experience - previous experience could be a reference to a decision (audit judgment). This study aimed to determine the effects of gender, stress obedience, independence, time budget pressure, and the experience of auditors on audit judgment. This study uses a quantitative descriptive approach. The population in this study is the external auditor who worked in public accounting firms Surabaya of 60 people. A sampling technique that uses purposive sampling, in order to obtain 41 respondents. The data analysis technique used is multiple linear regression. The results showed that the partial variables: (1) Gender has a positive and significant impact on the Audit Judgment with sig (0.013 <0.05), (2) Pressure Obedience does not have a positive and significant impact on the Audit Judgment with sig (0882 <0.05), (3) Independence of positive and significant influence on the Audit Judgment with sig (0.048 <0.05), (4) time Budget pressure does not have a positive and significant impact on the Audit Judgment with sig (0076 <0 , 05), (5) experience auditors do not have a positive and significant impact on the Audit Judgment with sig (0433 <0.05). From the above results showed that only two variables that affect audit judgment, namely gender and independence.Keywords: Gender, Obedience Pressure, Independence, Time Budget Pressure, Experience Auditor, and Audit Judgment.